Mental Health Among Parents of Children With Critical Congenital Heart Defects: A Systematic Review. Issue 2 (2nd February 2017) - Woolf‐King, Sarah E.; Anger, Alexandra; Arnold, Emily A.; Weiss, Sandra J.; Teitel, David
Abstract : Background: Parents of children with critical congenital heart defects (PCCHDs) may be at high risk for mental health morbidity; however, the literature is not well characterized. Given that compromised parental mental health can lead to long‐term cognitive, health‐related, and behavioral problems in children, a systematic review of this literature could provide informed recommendations for continued research and enhance the care of families of children living with critical congenital heart defects. Methods and Results: We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines that resulted in 30 studies on the mental health of PCCHDs. The literature revealed that PCCHDs are at an elevated risk for psychological problems, particularly in the immediate weeks and months following cardiac surgery. Up to 30% of PCCHDs have symptoms consistent with a diagnosis of posttraumatic stress disorder, with over 80% presenting with clinically significant symptoms of trauma; 25% to 50% of PCCHDs reported clinically elevated symptoms of depression and/or anxiety, and 30% to 80% reported experiencing severe psychological distress. There was high variability in measurements used to assess study outcomes, methodological quality, and sociocultural composition of the parents included in the studies. Conclusions: There is an urgent need for additional research on the severity, course, persistence, and moderators of these mental health problems over time, and for the development and testing of screening approaches and interventions that can be feasibly delivered in the context of ongoing pediatric cardiac care.